Effect of age and scrotal circumference on sperm morphology in Brahman bulls using a modified fixation technique - Sevilla, Francisco; Araya-Zúñiga, Ignacio; Salamanca-Carreño, Arcesio; Silvestre, Miguel A.; Rodríguez, Julio; Matamoros, Kenneth; Molina-Montero, Rafael; Carranza-Rojas, Luis C.; Roldan, Eduardo R. S.; Valverde, Anthony (Frontiers in Veterinary Science, 2025)
Sperm morphology (form and size of sperm) analysis is useful for evaluating bull fertility and diagnosing reproductive performance. An advanced age is associated with a higher frequency of morphological sperm anomalies; however, there is limited information on the effect of aging and scrotal circumference on sperm morphological defects in Brahman cattle. The objective of this study was to investigate changes related to age and scrotal circumference on sperm morphology in Brahman bulls in Costa Rica. Brahman bulls are traditionally used in Costa Rican production systems. Sperm morphology was evaluated in 51 Brahman bulls from six age groups (< 24, 24–36, 37–48, 49–60, 61–72, and >72 months old) and scrotal circumference (32–36, 37–41, 42–46, and > 47 cm). The Trumorph® system was used for fixation. A total of 112 ejaculates and 200 sperm cells were analyzed per sample. Sperm defects were classified according to the 2021 World Health Organization laboratory manual and classification of University of Queensland Sperm Morphology Standardization Program. There was a higher frequency of anomalies in younger bulls (< 24 months old) and in those with a scrotal circumference >47 cm. A significant variation was found between the years analyzed, with significant differences (p < 0.05) of the year 2022 with respect to the others years. The most common defects by sperm region were loose heads and nuclear vacuoles, distal midpiece reflex, and bent tails. Deterioration related to age and scrotal circumference was observed in sperm morphology, with a higher defect frequency in bulls under 24 months of age and in those with a scrotal circumference >47 cm. Sperm morphology in Brahman bulls showed similar incidence regardless of sexual status (breeding or resting), but they varied according to age and scrotal circumference.